Isokinetic rotator muscles fatigue in glenohumeral joint instability before and after Latarjet surgery A pilot prospective study. Issue 2 (1st November 2012) - Edouard, P.; Bankolé, C.; Calmels, P.; Beguin, L.; Degache, F.
<x xml:space="preserve">Abstract</x> We aimed to analyze the changes in isokinetic internal (IR) and external (ER) rotator muscles fatigue (a) in patients with non‐operated recurrent anterior instability, and (b) before and after shoulder surgical stabilization with the Bristow–Latarjet procedure. Thirty‐seven patients with non‐operated unilateral recurrent anterior post‐traumatic instability (NG) were compared with 12 healthy subjects [control group (CG)]. Twenty patients with operated recurrent anterior instability group (OG) underwent isokinetic evaluation before and 3, 6, and 21 months after Bristow–Latarjet surgery. IR and ER muscles strength was evaluated with Con‐Trex® dynamometer, with subjects seated and at a 45° shoulder abduction angle in scapular plane. IR and ER muscle fatigue was determined after 10 concentric repetitions at 180°·s−1 through the fatigue index, the percent decrease in performance (DP), and the slope of peak torque decrease. There were no differences in rotator muscles fatigue between NG and CG. In OG, 3 months post‐surgery, IR DP of operated shoulder was significantly (P < 0.001) higher than presurgery and 6 and 21 months post‐surgery. Rotator muscles fatigability was not associated with recurrent anterior instability. After surgical stabilization, there was a significantly higher IR fatigability in the operated shoulder 3 months post‐surgery, followed by recovery evidenced 6 months post‐surgery and long‐term maintenance over 21 months.